(untitled) (Global Journal of Human-Social Science, 2025)
This article aims to analyze the conduct of Public Authorities in times of adversity which may have diverse origins ranging as discussed in this work from health crises to others of an eminently economic nature The parameters used will be the economic crisis of 2008 briefly discussed and the pandemic resulting from the new coronavirus COVID 19 Through an analysis of the legislation of Latin American countries Brazil Peru and Argentina with a focus on Brazilian federal legislation the need for direct intervention by the State in maintaining the constitutional order is shown especially in the social economic and public health aspects A brief comparative study on the actions of these countries in combating the pandemic The presence of the Regulatory State acts directly in the contingency of expenses to resize public priorities Therefore when faced with these situations the aim is to keep the Public Authorities fully operational and to reach the minimum civilizing levels within reach through the implementation of new public policies and those already underway preserving rights and guarantees already in effect Thus we seek to debate the State s responsibility in maintaining public economic and social order The bibliographic and documentary methodology and a qualitative approach of a theoretical nature were used to carry out this research